Sulfated Carbon Quantum Dots as Efficient Visible‐Light Switchable Acid Catalysts for Room‐Temperature Ring‐Opening Reactions1. (1st June 2015) - Li, Haitao; Sun, Chenghua; Ali, Muataz; Zhou, Fengling; Zhang, Xinyi; MacFarlane, Douglas R.
Abstract Acid catalytic processes play a classic and important role in modern organic synthesis. How well the acid can be controlled often plays the key role in the controllable synthesis of the products with high conversion yield and selectivity. The preparation of a novel, photo‐switchable solid‐acid catalyst based on carbon quantum dots is described. The carbon quantum dots are decorated with small amounts of hydrogensulfate groups and thus exhibit a photogenerated acidity that produces a highly efficient acid catalysis of the ring opening of epoxides with methanol and other primary alcohols. This reversible, light‐switchable acidity is shown to be due to photoexcitation and charge separation in the carbon quantum dots, which create an electron withdrawing effect from the acidic groups. The catalyst is easily separated by filtration, and we demonstrate multiple cycles of its recovery and reuse.